NRF2-directed PRPS1 upregulation to promote the progression and metastasis of melanoma - Xiong, Guohang; Feng, Yu; Yi, Xiaojia; Zhang, Xuedan; Li, Xiaoyu; Yang, Lijuan; Yi, Zihan; Sai, Buqing; Yang, Zhe; Zhang, Qiao; Kuang, Yingmin; Zhu, Yuechun (Frontiers in Immunology, 2022)
Phosphoribosyl pyrophosphate synthetase 1 (PRPS1) is the first enzyme in the de novo purine nucleotide synthesis pathway and is essential for cell development. However, the effect of PRPS1 on melanoma proliferation and metastasis remains unclear. This study aimed to investigate the regulatory mechanism of PRPS1 in the malignant progression of melanoma. First, our data confirmed that PRPS1 was upregulated in melanoma and melanoma cells. Next, CCK-8, colony formation, EdU, RT–PCR, western blot, and cell cycle assays, as well as nude mice data indicated that PRPS1 could promote the proliferation of melanoma both in vitro and in vivo. In addition, RT–PCR, western blot, and flow cytometry analyses indicated that PRPS1 inhibited melanoma cell apoptosis. PRPS1 increased the migration and invasion of melanoma cells, as shown by cell scratch, Transwell migration/invasion, western blot and experimental pulmonary metastasis assays in vivo. Furthermore, the regulatory function of NRF2 on PRPS1 was explored by ChIP–qPCR and luciferase reporter assays. These results suggest that NRF2 could bind to the PRPS1 promoter and increase PRPS1 transcription. Taken together, the results of this study validate that PRPS1 can be activated by NRF2 and promote the proliferation and metastasis of melanoma.